Ultrashort baseline synchronous-clock emergency resynchronizing method in the Jiaolong deep-sea manned submersible. (12th February 2019) - Zhang, Tongwei; Liu, Baohua; Liu, Yeyao; Tang, Jialing; Qin, Shengjie; Wang, Xiangxin
During the dive operation of the Jiaolong deep-sea manned submersible, the synchronization clock in the manned cabin may be falsely triggered and cause asynchrony between it and the synchronization clock installed in the mothership, rendering it impossible for the ultrashort baseline to provide the correct position of the Jiaolong deep-sea manned submersible. To solve this problem, this article proposes an emergency resynchronizing method for the two synchronous clocks, used by the ultrashort baseline, in the Jiaolong deep-sea manned submersible. Initially, based on the depth and horizontal range measured by the ultrashort baseline and the manned submersible depth transmitted by the acoustic communication system, the time-delay difference between the two synchronous clocks is estimated. The time-delay difference is then compensated by delaying the synchronous clock trigger signal by an external waveform generator in the mothership. Finally, by comparing the depth measured by the ultrashort baseline and the manned submersible depth transmitted by the acoustic communication system, the time-delay difference is finely adjusted. Using this method, the ultrashort baseline problem, which occurred suddenly while the Jiaolong deep-sea manned submersible was diving, is successfully solved.